All-optical exclusive NOR logic gate using Mach-Zehnder interferometer - Lee, S; Park, J; Lee, K; Eom, D; Lee, S; Kim, JH (JAPAN SOC APPLIED PHYSICS, 2002)
In this paper, we propose an all-optical exclusive NOR (XNOR) gate for the first time, which uses an integrated semiconductor-optical-amplifier-based Mach-Zehnder interferometer. The operation of the proposed all-optical XNOR logic gate is experimentally demonstrated at 10 Gbit/s.
Keywords: WAVELENGTH CONVERTER; XOR